2010
DOI: 10.1007/978-1-60761-934-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Escalation of Drug Use

Abstract: Among the different behavioral criteria used to discriminate substance dependence (or drug addiction) from other non-disordered forms of drug use, drug intake escalation presents a number of unique features that makes it particularly suitable for modeling in nonhuman animals. This criterion has stood the passage of time despite major revisions of diagnostic systems, it is common to all known drugs of abuse and it can be readily and unambiguously operationalized in laboratory animals. Here I exhaustively review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 119 publications
1
53
0
Order By: Relevance
“…SEM, standard error of the mean Finally, using a conditioned emotional suppression procedure, Vanderschuren and Everitt (2004) found that after extended drug use rats were more likely to continue to seek cocaine despite the presence of a danger signal that normally suppresses operant behavior. Similarly, we recently found that after punishment by footshock rats with extended access to cocaine resumed drug self-administration more rapidly than controls, which refrained from self-administering cocaine for at least 3 consecutive days (Ahmed 2011).…”
Section: Figurementioning
confidence: 97%
See 3 more Smart Citations
“…SEM, standard error of the mean Finally, using a conditioned emotional suppression procedure, Vanderschuren and Everitt (2004) found that after extended drug use rats were more likely to continue to seek cocaine despite the presence of a danger signal that normally suppresses operant behavior. Similarly, we recently found that after punishment by footshock rats with extended access to cocaine resumed drug self-administration more rapidly than controls, which refrained from self-administering cocaine for at least 3 consecutive days (Ahmed 2011).…”
Section: Figurementioning
confidence: 97%
“…Escalation of cocaine intake is largely due to acceleration in the rate of cocaine self-administration. Adapted and modifi ed from Ahmed (2005Ahmed ( , 2011. SEM, standard error of the mean Finally, using a conditioned emotional suppression procedure, Vanderschuren and Everitt (2004) found that after extended drug use rats were more likely to continue to seek cocaine despite the presence of a danger signal that normally suppresses operant behavior.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Ironically, however, by focusing attention on drug use initiation, this model has contributed, perhaps more than any other models, to blur the distinction between mere drug use and addiction and thus retard progress in this area. If anything, the LR-HR model may be considered a model of transition from initial abstinence to recreational drug use, but certainly not a model of transition to escalated drug use (Ahmed 2011;Ahmed and Koob 1998). It remains to be demonstrated whether HR rats are more vulnerable than LR rats to escalation of drug use under extended access conditions.…”
mentioning
confidence: 99%